Power from the Desert: Not a Mirage - Claudia Kemfert; Wolf-Peter Schill (Weekly Report, 2009)
Energy policy is confronted by two major challenges. First, fossil fuels will become ever more scarce and expensive in coming years, a trend which will intensify conflicts for the control of natural resources. Second, the burning of fossil fuels-particularly coal-is leading to an increase in harmful greenhouse gas emissions. To address these challenges, the share of renewable energy in total energy consumption must be considerably increased. In sharp contrast to fossil fuels, which are becoming ever more depleted, renewable energy sources are essentially inexhaustible. Furthermore, renewable energy produces hardly any greenhouse gases. The large-scale exploitation of solar energy for power generation offers enormous potential. In theory, solar-thermal collectors installed in North Africa over an area roughly the size of New Jersey could meet all of Europe's electricity needs. The construction of high-voltage direct current (HVDC) lines would be necessary to import power from the Mediterranean region without excessive transmission losses. An expansion of European electricity networks could also yield supplementary benefits, including enhanced integration of domestic renewable energy (such as wind power), and improved competition in electricity markets.
Keywords: Q40; L94; Q42; P28; 330; Electricity trade; Solar energy; DESERTEC